Natural resources used as folk cosmeceuticals among rural communities in Vhembe district municipality, Limpopo province, South Africa - Mamokete Venolia Setshego; Adeyemi Oladapo Aremu; Obakeng Mooki; Wilfred Otang-Mbeng (BMC, 2020)
Abstract Background Skin-related diseases affect every individual irrespective of age, gender or social status. Since time immemorial, humans have explored natural resources from their environment for the maintenance of the skin. This explorative survey was conducted to document the natural resources (plant and non-plant materials) used for folk cosmeceuticals by rural communities in Vhembe district municipality, Limpopo province, South Africa. Methods The research was conducted in six communities namely: Tshakuma, Shigalo, Tshamutilikwa, Luvhimbi (Masikhwa), Khakhanwa, and Folovhodwe in Vhembe district. Random and convenient sampling was used to access the target population. Semi-structured questionnaires were used to interview 71 participants that comprised traditional practitioners, herbalists and laypeople from the study area. Collected data were analysed using both quantitative (for e.g. frequency, use-value and relative frequency of citation) and qualitative (thematic) analytical methods. Results A total of 52 plants from 27 families and 22 non-plant materials were used as folk cosmeceuticals in the study area. The most cited plants included Dicerocaryum zanguebarium (Pedaliaceae), Ricinus communis (Euphorbiaceae) and Helinus integrifolius (Rhamnaceae). Trees and shrubs were the most common plant-life form while leaves were the most popular plant part. Pig fats, red ochre (Luvhundi soil) and ashes were the most cited non-plant materials. These documented natural resources are frequently prepared by crushing and mostly used to heal wounds. Conclusion Traditional knowledge concerning folk cosmeceuticals is mostly held by elders. The high number of natural resources documented is an indication that Vhembe district is rich in ethnopharmacological knowledge. Scientific investigation of the efficacies and safety of these natural resources is highly recommended as a drive aimed at innovations with benefits to the rural communities who are the custodians of this valuable knowledge.